1994
DOI: 10.1002/bbpc.19940981213
|View full text |Cite
|
Sign up to set email alerts
|

The T,x,p‐phase diagram of binary phospholipid mixtures

Abstract: High pressure differential thermal analysis (MA) has been applied to the study of the temperature-composition-pressure phase diagram of the binary saturated phospholipid mixtures dimyristoyl/palmitoyl phosphatidylcholine (DMPC/DPPC) and dimyristoyl/stearoyl phosphatidylcholine (DMPCIDPPC) in excess water. A temperature range from 10 to 100°C and a pressure range from ambient up to 1500 bar has been covered. The experimentally obtained phase equilibria of these binary systems are compared with thermodynamic cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…18 at 1 bar a slope of À3.3 AE 0.1 is obtained which yields a surfacefractal dimension of D s 2.7 AE 0.1. With increasing pressure, the gel-fluid coexistence region of a DMPC/DSPC mixture is shifted toward higher temperatures (Landwehr, Winter, 1994b). A shift of about 22 C/kbar is observed, similar to the slope of the gel-fluid transition line of the pure components (Fig.…”
Section: Phase-separated Phospholipid Mixturesmentioning
confidence: 55%
“…18 at 1 bar a slope of À3.3 AE 0.1 is obtained which yields a surfacefractal dimension of D s 2.7 AE 0.1. With increasing pressure, the gel-fluid coexistence region of a DMPC/DSPC mixture is shifted toward higher temperatures (Landwehr, Winter, 1994b). A shift of about 22 C/kbar is observed, similar to the slope of the gel-fluid transition line of the pure components (Fig.…”
Section: Phase-separated Phospholipid Mixturesmentioning
confidence: 55%
“…The pressure dependence of the melting transition has been investigated before by various authors. 12,13,16,[18][19][20][21]36,37 It has been shown that the shift of the lipid melting transition is linear with the applied hydrostatic pressure in a pressure range up to at least 2 kbar. However, these authors were mainly interested in the shift of the transition point.…”
Section: Discussionmentioning
confidence: 99%
“…depending on their molecular structure, hydration level, pH, ionic strength, temperature and pressure. 14,15,[20][21][22][23][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] The basic structural element of biological membranes consists of a lamellar phospholipid bilayer matrix (Fig. 2a).…”
Section: Lipid Self-assemblymentioning
confidence: 99%
“…In addition to these thermotropic phase transitions, a variety of pressure-induced phase transformations have been observed. [26][27][28][30][31][32][33] Because the average end-to-end distance of disordered hydrocarbon chains in the L a -phase is smaller than that of ordered (all-trans) chains, the bilayer becomes thinner during melting at the P b 0 /L a -transition, even though the partial lipid volume increases. This is demonstrated in Fig.…”
Section: Lipid Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation